Cucurbit[6]uril‐Derived Nitrogen‐Doped Hierarchical Porous Carbon Confined in Graphene Network for Potassium‐Ion Hybrid Capacitors. Issue 20 (26th August 2020) - Qiu, Daping; Guan, Jingyu; Li, Min; Kang, Cuihua; Wei, Jinying; Wang, Feng; Yang, Ru
Abstract: Potassium‐ion hybrid capacitors (PIHCs) have attracted tremendous attention because their energy density is comparable to that of lithium‐ion batteries, whose power density and cyclability are similar to those of supercapacitors. Herein, a pomegranate‐like graphene‐confined cucurbit[6]uril‐derived nitrogen‐doped carbon (CBC@G) with ultra‐high nitrogen‐doping level (15.5 at%) and unique supermesopore‐macropores interconnected graphene network is synthesized. The carbonization mechanism of cucurbit[6]uril is verified by an in situ TG‐IR technology. In a K half‐cell configuration, CBC@G anode demonstrates a superior reversible capacity (349.1 mA h g −1 at 0.1 C) as well as outstanding rate capability and cyclability. Moreover, systematic in situ/ex situ characterizations, and theory calculations are carried out to reveal the origin of the superior electrochemical performances of CBC@G. Consequently, PIHCs constructed with CBC@G anode and KOH‐activated cucurbit[6]uril‐derived nitrogen‐doped carbon cathode demonstrate ultra‐high energy/power density (172 Wh kg −1 /22 kW kg −1 ) and extraordinary cyclability (81.5% capacity retention for 5000 cycles at 5 A g −1 ). This work opens up a new application field for cucurbit[6]uril and provides an alternative avenue for the exploitation of high‐performance PIHCs. Abstract : An advanced potassium‐ion hybrid capacitor that integrates high energy density, high power density, and outstanding cyclability is constructed with graphene‐confined cucurbit[6]uril‐derived nitrogen‐doped carbon anode and KOH‐activated cucurbit[6]uril‐derived nitrogen‐doped carbon cathode.